2018 IEEE International Conference on Industrial Electronics for Sustainable Energy Systems (IESES) 2018
DOI: 10.1109/ieses.2018.8349932
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing standardization needs for CHIL-based testing of power systems and components

Abstract: Real-time simulation methods for investigations on electric networks and integration of grid connected generation units are increasingly in the focus of ongoing research areas. While laboratory testing methods are the predominant method for the verification of safety and quality related features of gridconnected generation units in the past, load flow modeling verification methods have been integrated in state-of-the-art standardization frameworks recently. The next step is comprised in real-time simulation me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This system integration testing needs to bridge the gap between simulations and field trials and is done in a laboratory. In this context, the concept of digital twin already used in factory automation domain [46] needs to be applied. The reason for this is that due to the amount of possibilities a field test to assess the performance every solution and device would not be possible or at least very time consuming and expensive.…”
Section: Laboratory-based Testing Of Energy Infrastructurementioning
confidence: 99%
See 1 more Smart Citation
“…This system integration testing needs to bridge the gap between simulations and field trials and is done in a laboratory. In this context, the concept of digital twin already used in factory automation domain [46] needs to be applied. The reason for this is that due to the amount of possibilities a field test to assess the performance every solution and device would not be possible or at least very time consuming and expensive.…”
Section: Laboratory-based Testing Of Energy Infrastructurementioning
confidence: 99%
“…It can be concluded that HIL simulations became an advanced means for investigative experimentation, model validation, and testing before implementation of electrical subsystems in actual processes [53]. This is reflected in the ongoing standardization efforts [46].…”
Section: Chil Applications and Examplesmentioning
confidence: 99%
“…Background knowledge of the CHIL simulation methodology and its design principles are presented in [22,23]. The authors discuss different CHIL setups used for generation units and network investigations.…”
Section: Introductionmentioning
confidence: 99%